(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the importance of digital technologies as a necessary condition for the formation of the readiness of future teachers for methodological work, and also emphasizes the importance of paying special attention to the gradual introduction of information and communication technologies into the educational process and improving the system of training programmers in accordance with modern requirements.